2009
DOI: 10.1111/j.1365-2966.2008.14251.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspect angle for interstellar magnetic field in SN 1006

Abstract: A number of important processes taking place around strong shocks in supernova remnants (SNRs) depend on the shock obliquity. The measured synchrotron flux is a function of the aspect angle between interstellar magnetic field (ISMF) and the line of sight. Thus, a model of non-thermal emission from SNRs should account for the orientation of the ambient magnetic field. We develop a new method for the estimation of the aspect angle, based on the comparison between observed and synthesized radio maps of SNRs, maki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 14 publications
10
80
0
Order By: Relevance
“…A strong axisymmetric background ISM magnetic field (not included in our simulations) has also been suggested to be responsible for the bilateral character of some Galactic supernova remnants (Gaensler 1998). It would indeed make their shape more elongated as long as the field is strong enough (Rozyczka & Tenorio-Tagle 1995) and produce X-ray and/or radio synchrotron emission from the opposed arcs (Velázquez et al 2004;Petruk et al 2009;Schneiter et al 2010).…”
Section: Bilateral Supernova Remnantsmentioning
confidence: 99%
“…A strong axisymmetric background ISM magnetic field (not included in our simulations) has also been suggested to be responsible for the bilateral character of some Galactic supernova remnants (Gaensler 1998). It would indeed make their shape more elongated as long as the field is strong enough (Rozyczka & Tenorio-Tagle 1995) and produce X-ray and/or radio synchrotron emission from the opposed arcs (Velázquez et al 2004;Petruk et al 2009;Schneiter et al 2010).…”
Section: Bilateral Supernova Remnantsmentioning
confidence: 99%
“…Recently, Petruk et al (2009b) have further investigated this problem, and showed that in the framework of a simple model of SN1006 in terms of a point-like explosion occurring in a uniform density and uniform magnetic field medium, there is no way to reconcile the quasi-parallel scenario and the SN1006 morphology as observed in the radio band. The same conclusion was reached more recently by Schneiter et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…The presence (or absence) of the Xray emission in the precursor gives hints on the particle acceleration properties (Long et al 2003;Morlino et al 2010;Winkler et al 2014). The azimuthal variation of the radio brightness depends on the obliquity dependence of the injection efficiency (Fulbright & Reynolds 1990;Petruk et al 2009a) while the X-ray azimuthal profile might help in determining whether the maximum particle momentum is timeor loss-limited (Petruk et al 2011a). High spatial resolution observations may reveal the distance between the shock and the contact discontinuity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they allow for determination of the 3-dimensional orientation of ISMF and even its gradient around SN 1006 (Petruk et al 2009a;Bocchino et al 2011) or, by analyzing a sample of SNRs, to reveal properties of the Galactic MF (West et al 2016). By modeling the surface brightness maps, it was shown that a certain class of SNRs, namely the thermal X-ray composites (or mixed-morphology SNRs, i.e.…”
Section: Introductionmentioning
confidence: 99%